Swarm Intelligence for Perception Layer Design of Internet of Things - Chuanyun Wang; Enyan Sun; Feng Tian; Na Lin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Internet of Things is the extension and expansion of Internet from the virtual world to the real world, in which a large number of resource-constrained devices are used to collaborative perception, and it identifies objects and gathers information in the case of no centralized control, no global model. However, the swarm intelligence can take advantage of many simple autonomous individuals to exhibit complex emergent behaviors. In this paper, the characteristics and commonality of perception layer and swarm intelligence were analyzed firstly, and then the architecture of smart individual, self-organization modeling, swarm behavior emergence pattern were analyzed and designed. Finally, intelligentization for perception layer was achieved on the support of middleware. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.4149